РЕБРЕНДИНГ ВУЗОВСКОЙ БИБЛИОТЕКИ КАК НОВЫЙ ВИТОК В ЕЕ РАЗВИТИИ: (НА ПРИМЕРЕ НАУЧНОЙ БИБЛИОТЕКИ ASEM) - РАЙЛЯН, доктор экономики, Молдавская Экономическая Академия, Елена (BIBLIOPOLIS, 2020)
The article highlights the role and the importance of university libraries and the need to promote and to rebrand them on the information market. The author offers basic promotion tools for the Scientific Library of AESM. The article covers requirements for staff that is responsible for promoting the library and information services.